Modifikasi Pengepingan Skema Leap Frog dalam Penentuan Karakteristik Profil Aliran Sungai dalam Mendukung Pemetaan Wilayah Banjir (Penelitian Awal) - Andy Eka Saputra; Didik Kuswadi (Jurnal Ilmiah Teknik Pertanian - TekTan, 2013)
In this study carried out by modifying the method LeapFrog split with The split the regulator equation St. Venant 1 dimensions. The factors used are data stream land cover and slope/contour. Rain put a lateral discharge equation while the discharge from upstream continuity included as a boundary condition on the grid points of the river. The final goal in future studies to produce an split which can be used to determine the flow profile characteristics of a river, so as to support the handling of flooding in the area desired nonstructure From the results of research conducted a few things that can be described Modifications made split Leap Frog has been successfully split the continuity equation and momentum with the results split. The split results for the continuity equationÂ The split above results in the early stages this research in trying to in Microsoft Fortran programs running on 6.5 and at this early study tested a simple case of the trapezoidal cross section of the river as well as data supporting data retrieved from the data Sekampung river as an example the case for programs to run and found that the results are already responding injection split discharge Q Nakayasu Sekampung well with characteristic output the shape of the profile of the river flow and results split with Microsoft Fortran 6.5 program that is in use is generally obtained water discharge (Q) outputs the same program with a discharge Q Nakayasu with repeated time 50 years of segment 0 m at the river until 21 hour simulation model has the same result as shown in Table 4 (table discharge results of running the program), so that the program is appropriate and can be running on the characteristics of the next river.Keywords: leap frog, st venant, flood modelling, lateral discharge, boundary conditions, nakayasu